Lack of Androgen Receptor Expression Selects for Basal-Like Phenotype and Is a Predictor of Poor Clinical Outcome in Non-Metastatic Triple Negative Breast Cancer - Riaz, Nazia; Idress, Romana; Habib, Sadia; Lalani, El-Nasir (Frontiers in Oncology, 2020)
Background: Androgen receptor (AR) has emerged as a significant favorable prognostic indicator in estrogen receptor expressing (ER+) breast cancer (BCa), however, its clinical and biological relevance in triple negative breast cancer (TNBC) and association with cancer stem cell (CSC) markers remains ambiguous. Methods: We examined the immunohistochemical expression of AR in a cohort of stage I-III TNBC cases (n=197) with a long-term clinical follow-up data (mean follow-up=53.6 months). Significance of AR expression was correlated with prognostic biomarkers including cancer stem cell markers (CD44, CD24 and ALDH1), basal markers (CK5, CK14 and nestin), proliferation marker (ki-67), apoptotic marker (Bcl-2) and COX-2. Expression of CK5 and nestin was used for categorization TNBC into basal (TN, CK5+ and/or nestin+) and non-basal (TN, CK5- and/or nestin-) phenotypes and Kaplan Meir curves were used for estimation of overall survival and breast cancer specific survival (BCSS). Results: AR expression was observed in 18.8% of non-metastatic TNBC tumors. Expression of AR correlated with lower grade (P < 0.001) and conferred a favorable prognostic significance in patients with axillary lymph node metastasis (P = 0.005). Lack of AR expression correlated with expression of CSC phenotype (CD44+/CD24-) (P < 0.001), COX-2 (P = 0.02), basal markers (CK5: P = 0.03) and nestin: P = 0.01). Basal like phenotype (TN, CK5+ and/or nestin+) correlated with quadruple negative breast cancer (QNBC) and showed a significant association with adverse prognostic markers including high proliferation index (P < 0.001), expression of COX-2 (P = 0.009) and CSC phenotype (CD44+/CD24- : P = 0.01). Expression of AR remained an independent prognostic indicator for improved overall survival (P =0.003), whereas basal like phenotype was associated with an adverse BCSS (P = 0.013). Conclusions: Assessment of AR and basal markers identified biologically and clinically distinct subgroups of TNBC. Expression of AR defined a low-risk TNBC subgroup associated with improved overall survival, whereas expression of basal markers (CK5 and nestin) identified a high-risk subgroup associated with adverse BCSS. Integration of immunohistochemical analysis of AR and basal biomarkers to the assessment of TNBC tumors is expected to improve the prognostication of an otherwise heterogenous disease.